Relationship of Benzene Concentration, ECR Benzene, Malondialdehyde, Glutathione, and DNA Degeneration in Shoe Industrial Workers in Osowilangun, Indonesia - Abdul Rohim Tualeka; Ng Yee Guan; Syamsiar S. Russeng; Ahsan Ahsan; Indri H. Susilowati; Pudji Rahmawati; Khusnul Ain (SAGE Publishing, 2020)
In the shoes industry, benzene constitute as one of the source of chemical hazard especially used in the gluing section. This compound is metabolized by the liver, forming free radicals in the body which can ultimately reduce the concentration of glutathione and increased malondialdehyde causing DNA degeneration. The purpose of this study was to determine the relationship between benzene concentration, excess cancer risk (ECR), malondialdehyde, glutathione, and DNA degeneration among workers in shoes industry in Osowilangun, Surabaya. This is an observational study with a cross-sectional design. The number of research samples was 25 respondents. The average concentration of benzene in workers was above the threshold (10.31 ppm). There were 15 (60%) respondents with ECR >0.0001 who experienced DNA degeneration. There was no relationship between benzene concentration, malondialdehyde, glutathione, and DNA degeneration. However, there was a relationship between benzene ECR, malondialdehyde, glutathione, and DNA degeneration in the shoe industry workers in Osowilangun.